2014
DOI: 10.1016/j.jacc.2013.07.110
|View full text |Cite
|
Sign up to set email alerts
|

Response to Prasugrel and Levels of Circulating Reticulated Platelets in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: The proportion of circulating RPs strongly correlates with response to prasugrel in patients with STEMI treated with PCI. High levels of RPs are associated with increased platelet reactivity despite prasugrel treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 18 publications
7
60
1
2
Order By: Relevance
“…However, larger and randomized studies are necessary for proving that these concepts are effective and safe in clinical practice. There are also indications that it is preferentially immature platelets that are recruited into arterial thrombi [106] and if confirmed, this finding may have consequences for treatment with antiplatelet drugs [107].…”
Section: Clinical Utility Of Reticulated/ Immature Plateletsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, larger and randomized studies are necessary for proving that these concepts are effective and safe in clinical practice. There are also indications that it is preferentially immature platelets that are recruited into arterial thrombi [106] and if confirmed, this finding may have consequences for treatment with antiplatelet drugs [107].…”
Section: Clinical Utility Of Reticulated/ Immature Plateletsmentioning
confidence: 98%
“…The current literature seems to provide preliminary support for the clinical utility of retPLT or IPF determinations, for risk assessment in acute coronary syndrome [100][101][102][103][104] as well as for monitoring drug treatment of coronary artery disease [78,79,[105][106][107]. However, larger and randomized studies are necessary for proving that these concepts are effective and safe in clinical practice.…”
Section: Clinical Utility Of Reticulated/ Immature Plateletsmentioning
confidence: 99%
“…В исследовании Перла (Perl) и соавт. [46] были также получены поло-жительные корреляции между содержанием ретикулярных тромбоцитов и остаточной аг-регационной активностью тромбоцитов при применении прасугрела. Однако в более позд-ней работе (выполненной сходным составом ав-торов) таких корреляций выявлено не было [47].…”
Section: ретикулярные тромбоциты у больных с сердечно-сосудистыми патunclassified
“…6 For patients with poor-risk disease features, including those with secondary AML (related to therapy or arising from an antecedent myeloid neoplasm) or adverse cytogenetics, the prognosis remains particularly bleak: with conventional chemotherapy, complete remission (CR) is achieved in fewer than 50% of cases (compared to 80% of patients with nonpoor-risk disease), and long-term survival remains at around 10%. 7 Several approaches have been adopted to improve responses to induction therapy that involve maneuvres designed to recruit leukemia cells synchronously into the cell cycle and thus render them potentially more sensitive to cell cycle-specific cytotoxic agents such as cytarabine. One study in younger adults with AML suggested that the cytotoxicity of induction chemotherapy could be enhanced in this way through the concurrent addition of granulocyte colony stimulating factor (G-CSF), although reported improvements in disease-free survival did not translate into an OS benefit.…”
Section: Editorialsmentioning
confidence: 99%
“…This increased thrombotic potential seems to be due to their content of cytosolic mRNA that is translationally active, which enables the expression of ADP receptors and prothrombotic factors. The number of juvenile platelets inversely correlates with responsiveness to clopidogrel 6 and prasugrel, 7 and also predicts adverse cardiovascular prognosis and future ACS. 8 Whether levels of juvenile platelets are a marker of risk or a risk factor 9 for ACS has still not been clarified.…”
mentioning
confidence: 99%